Croatia - Policy Notes : A Strategy for Smart, Sustainable and Inclusive Growth - World Bank (Washington, DC, 2013)
Signing the accession treaty with the European Union (EU) and its forthcoming membership to the EU are remarkable opportunities for Croatia to address a number of economic challenges and join the EU as a competitive and successful economy. The new Croatian government in its program for 2011-2015 seeks higher standards of living for its citizens through sustained economic growth and greater social cohesion. Given the legacies from the past, these tasks will require ambitious and credible policy decisions. Once it joins the EU, Croatia will also have to contribute to the Europe 2020 strategy for smart, sustainable and inclusive growth which calls on member states to set national targets in employment, innovation, education, social inclusion and climate or energy. These targets will also require concerted efforts in structural reforms by the Government of Croatia. A major priority for the coming two to three years will be to create fiscal space to absorb EU funds and avoid being a net contributor to the EU. Upon accession, the EU Structural and Cohesion funds available to Croatia will exceed Euro 1.5 billion a year. At the same time, Croatia will also be obliged to contribute about 680 million annually to the EU budget. A number of new member states have found it a challenge to access and absorb EU funds effectively and efficiently. This requires a lot of preparatory work to get projects ready now for the time when EU structural and cohesion funds can be accessed, as they represent a huge increase over pre-accession funds and a great opportunity to address Croatia's needs in transport and environment, as well as in innovation and modernization of production.